Case Report: Compound Heterozygous Variants in MOCS3 Identified in a Chinese Infant With Molybdenum Cofactor Deficiency - Tian, Qi; Cao, Yang; Shu, Li; Chen, Yongjun; Peng, Ying; Wang, Yaqin; Chen, Yuanyuan; Wang, Hua; Mao, Xiao (Frontiers in Genetics, 2021)
Background The molybdenum cofactor (Moco) deficiency in humans results in the inactivity of molybdenum‐dependent enzymes and was caused by pathogenic variants in MOCS1, MOCS2 and GPHN. These genes along with MOCS3 are involved in Moco biosynthesis and providing cofactors to Moco dependent enzymes. Until now, there was no study to confirm that MOCS3 is a causative gene of Moco deficiency. Methods Detailed clinical information was collected in the pedigree. The Whole-exome sequencing (WES) accompanied with Sanger sequencing validation were performed. Results We described the clinical presentations of an infant, born to non-consanguineous healthy family, diagnosed as MOCS3 variants caused Moco deficiency and showed typical features of Moco deficiency including severe neurologic symptoms, cystic encephalomalacia in brain MRI and resulted in neonatal death. Compound heterozygous variants in MOCS3 gene was identified by WES. Positive sulfite and decreased level of uric acid in plasma and urine were detected. Conclusion To our knowledge, this is the first case of MOCS3 variants caused Moco deficiency. Our study may contribute to genetic diagnosis of Moco deficiency and future genetic counselling.